Temperature-stress-time methodology for flat-patterning ETFE cushions in use for large-span building structures. (1st February 2020) - Hu, Jianhui; Chen, Wujun; Li, Yipo; Qu, Yegao; Zhao, Bing; Yang, Deqing
Highlights: A creep model of ETFE foils in terms of T, σ and t is proposed and validated. Two cushions with inverse T and P are compared with experiments and simulations. Ratios (height to edge) larger than suggested ratio result in proper structural forms. Cushions with low P/high T is easier to achieve forms than Cushions with high P/low T. Abstract: Ethylene tetrafluoroethylene (ETFE) cushion structures with excellent building aesthetics and reasonable structural behavior can be utilized as roofs and facades of large-span building structures. The form and force of such structures interact due to structural flexibility and complexity. The determination of a suitable form needs form-finding and cutting pattern for conventional ETFE cushions, which incorporates complex theoretical analysis and fabrications. To obtain a structural form without complex cutting pattern, a flat-patterning ETFE cushion is proposed based on creep properties of polymer materials. This methodology facilitates to achieve desired forms using creep models of ETFE foils. Moreover, time-temperature superposition of polymer materials is employed to improve this method. Therefore, this paper focuses on a modified creep model of ETFE foils and utilizes it to assess form and force of flat-patterning ETFE cushion structures. The Bailey-Norton model with Modified Time Hardening effect results in a creep model that describes creep strains at high temperature. To integrate this model into software, a multi-linear model is used where parameters are determined with experimental results. The related numerical simulations demonstrate the suitability of reproducing creep strains. For structural analysis, two typical cushions with inverse temperatures and pressures are simulated with multi-linear models. It is found that the maximum stress and strain exist near middle area of long edges and propagate towards cushion center. The final deformations of two cushions are 21.2 mm and 19.4 mm; the ratios of heights to edge length are larger than the engineering ratio of 1/8, resulting in a suitable structural form. A further ratio of stress to yield stress suggests the easy operation to achieve desired forms for small pressure at high temperature than large pressure at low temperature. In general, the proposed method to reveal form and structural behavior is useful for promoting utilizations of flat-patterning ETFE cushions.